Calculation Analysis of Erosion Rates and Sedimentation Transport in the Liliba Watershed - Sri Santi L M F Seran; Agustinus H Patiraja; Krisantos Ria Bela; Azarya Bees; Muritius I R Naikofi (Publikasi Indonesia, 2024)
Erosion is the loss or erosion of land or parts of land from a place by water or wind. Erosion causes the loss of fertile soil layers that are good for plant growth and reduces the soil's ability to absorb and retain water. The Liliba watershed area in Kupang City includes Maulafa District, Oebobo District, Kelapa Lima District. The Liliba River Watershed (DAS) is part of the development of the Noelmina River area which flows into Oesapa Beach. The Liliba watershed has an area of 4,534 hectares with a main river length of 20,176.22 m. Using the USLE Method and SDR Transport Analysis, it was found that the erosion that occurred was 3.72 tonnes per year and the amount of sediment transport that occurred was 2.73 tonnes per year.